Radiation protection in Dentomaxillofacial Radiology Installation - Redzuan Lee, Mohammad Adib; Oscandar, Fahmi; Firman, Ria Noerianingsih (Padjadjaran Journal of Dentistry, 2014)
Introduction: ICRP produces recommendations for radiation protection concerning among them, patient, personnel and surrounding. The supervision for radiation protection in Dentomaxillofacial Radiology Installation RSGM-UNPAD and PP-UM must be as according to the national regulations. The purpose of study is how is the radiation protection and PP-UM, and what factors that influence radiation protection. Methods: Descriptive of qualitative research method with questionnaire technique with observational and interview survey, done to describe radiation protection with ALARA principle, taken in both Dentomaxillofacial Radiology Installation of RSGM-UNPAD and PP-UM. Result: Although few criteria like, lead apron lead protective glove, gonad lead barrier for personnel or operator, and, pass box and film storage for surrounding, radiation protection were not met by both installations, thyroid collar for patient radiation protection was met in PP-UM while not in RSGM-UNPAD. Conclusion: Radiation protection in Dentomaxillofacial Radiology Installation of RSGM-UNPAD have the advantage of systematic and central way of enforcement of regulation, and the weakness of its standard of radiation protection was not comprehensive, while PP-UM have the advantage of high supervision and adequate of instruments for patient radiation protection, and the weakness of its standard of radiation protection was not comprehensive. Factors influence the result were due to unavailable of SOP, insufficient of funds, inadequate of instruments, low supervision, and difficulty in bureaucracy approval.